Bone marrow-derived myeloid progenitors in the leptomeninges of adult mice. (11th December 2020) - Koeniger, Tobias; Bell, Luisa; Mifka, Anika; Enders, Michael; Hautmann, Valentin; Mekala, Subba Rao; Kirchner, Philipp; Ekici, Arif B.; Schulz, Christian; Wörsdörfer, Philipp; Mencl, Stine; Kleinschnitz, Christoph; et al.
Abstract: Although the bone marrow contains most hematopoietic activity during adulthood, hematopoietic stem and progenitor cells can be recovered from various extramedullary sites. Cells with hematopoietic progenitor properties have even been reported in the adult brain under steady-state conditions, but their nature and localization remain insufficiently defined. Here, we describe a heterogeneous population of myeloid progenitors in the leptomeninges of adult C57BL/6 mice. This cell pool included common myeloid, granulocyte/macrophage, and megakaryocyte/erythrocyte progenitors. Accordingly, it gave rise to all major myelo-erythroid lineages in clonogenic culture assays. Brain-associated progenitors persisted after tissue perfusion and were partially inaccessible to intravenous antibodies, suggesting their localization behind continuous blood vessel endothelium such as the blood-arachnoid barrier. Flt3 Cre lineage tracing and bone marrow transplantation showed that the precursors were derived from adult hematopoietic stem cells and were most likely continuously replaced via cell trafficking. Importantly, their occurrence was tied to the immunologic state of the central nervous system (CNS) and was diminished in the context of neuroinflammation and ischemic stroke. Our findings confirm the presence of myeloid progenitors at the meningeal border of the brain and lay the foundation to unravel their possible functions in CNS surveillance and local immune cell production. Abstract : This study identified a heterogeneous population of myeloid progenitors in the leptomeninges of adult mice, which gave rise to all major myelo-erythroid lineages in clonogenic assays. Lineage tracing and bone marrow transplantation showed that the progenitors were derived from adult hematopoietic stem cells and most likely continuously replaced via cell trafficking. Their numbers were diminished in the context of neuroinflammation.